Examen especial a los ingresos y gastos de la federación provincial de ligas deportivas barriales y parroquiales de Sucumbíos-Fedelibas, ubicada en la ciudad de Nueva Loja, cantón Lago Agrio, en el período 2014 - Sánchez Sánchez, Yessenia Verónica (2016)
This work will help improve the professional future, through the bond of the knowledge acquired in university education, provided an objective character, more of it will fulfill one of the requirements of the UNL Academic Regulations, for obtaining Engineer professional degree in Accounting and Auditing, CPA. With the Special Examination FEDELIBAS applied, it was possible to evaluate the internal control structure that keeps this institution regarding their income and expenditure; objective to be achieved through the implementation of Internal Control Standards for public and private entities. The process comprising a special examination from the previous visit, notifications, schedule of activities, narrative bonds, review, analysis and comparison of documents with the accounting records was developed to finally present a report reasonableness of balances determined income and expenditure accounts, the same as was structured through conclusions and recommendations to be considered by the board to take corrective action for errors in the process, registration or custody of the resources owned by FEDELIBAS. For these reasons, it is concluded that within the sports institution FEDELIBAS, there is no proper management and control of documentation and processes in which the different movements of the support accounts; this is due to the lack of manual functions, internal policies and strategies for staff working in this organization; so, managers it recommends that these requirements are vital to maintaining stability and prestige of the institution.